PERAN PANGERAN LANANG DANGIRAN DALAM PROSES ISLAMISASI DI SURABAYA PADA TAHUN 1595-1638 M - Devy Zulfa Rosyida; Muhdi (Qurthuba: The Journal of History and Islamic Civilization, 2022)
Abstract: This study aims to determine (1) the origin of Surabaya and its development in the 16th century AD to the 17th century AD, (2) the biography of Prince Lanang Dangiran, (3) the contribution of Prince Lanang Dangiran in the process of Islamization in Surabaya. This study uses historical research methods, which consist of heuristics, verification, interpretation and historiography. The approach used in this research is the historical approach proposed by Hasan Usman and the sociological approach proposed by Weber, while the theory uses the role theory according to Soerjono Soekanto. From the results of this study, it can be concluded that: (1) during the reign of the Majapahit Kingdom, Surabaya was the main port of the Majapahit Kingdom due to its strategic location in the Brantas River delta, (2) Prince Lanang Dangiran at the age of 18 meditated by throwing himself into the sea. Then left and settled in Surabaya in 1595 AD, then died in 1638 AD, (3) Prince Lanang Dangiran was a figure who had an important role in the spread of Islam in Surabaya, more precisely in North Surabaya. Keywords: Contribution, Prince Lanang Dangiran, Islamization Process